Dynamic rifle stability is not influenced by exercise intensity in young biathletes - Žák, M.; Struhár, I.; Janoušek, D.; Ondrácek, J. (Journal of Human Sport & Exercise, 2019)
The aim of the study was to analyse and find out potential dependence between the dynamic rifle stability during targeting and percentage pressure value on the trigger 1 second and 0.5 second before the shot in different intensities of the physical load. Fifteen national youth and junior elite biathletes (ten women, five men) from a team of the Czech Republic participated in the study. All participants completed measuring of the dynamic behavior of the rifle in rest and after roller skiing in three different exercise intensities: Intensity 1 = 70 % of HRmax (maximum heart rate), average speed 4.1 - 4.6 m·s-1; Intensity 2 = 80 % of HRmax, average speed 4.5 - 5.0 m·s-1; Intensity 3 = 90 % of HRmax, average speed 4.9 - 5.4 m·s-1. Each bout consisted from a distance of one km. They shot in standing position with using their own biathlons rifle with a fixed accelerometer and trigger sensor. The data used in our research showed that the dynamic rifle stability is not influenced by exercise intensity neither in the men nor women group. However, our study demonstrated that the rifle stability is better in time 0.5 second before the shot than in time 1 second before the shot. The measurement of triggering in our study showed that participants are able to work with their fingers on the triggers in similar quality in the racing load as well as without the previous physical load.